A Meta-Analysis of the Effect of Subthalamic Nucleus-Deep Brain Stimulation in Parkinson's Disease-Related Pain - Diao, Yu; Bai, Yutong; Hu, Tianqi; Yin, Zixiao; Liu, Huangguang; Meng, Fangang; Yang, Anchao; Zhang, Jianguo (Frontiers in Human Neuroscience, 2021)
Pain from Parkinson's disease (PD) is a non-motor symptom affecting the quality of life and has prevalence of 20–80%. However, it is unclear whether subthalamic nucleus deep brain stimulation (STN–DBS), a well-established treatment for PD, is effective forPD-related pain. Thus, the objective of this meta-analysis was to investigate the efficacy of STN-DBS on PD-related pain and explore how its duration affects the efficacy of STN-DBS. A systematic search was performed using PubMed, Embase, and the Cochrane Library. Nine studies included numerical rating scale (NRS), visual analog scale (VAS), or non-motor symptom scale (NMSS) scores at baseline and at the last follow-up visit and therefore met the inclusion criteria of the authors. These studies exhibited moderate- to high-quality evidence. Two reviewers conducted assessments for study eligibility, risk of bias, data extraction, and quality of evidence rating. Random effect meta-analysis revealed a significant change in PD-related pain as assessed by NMSS, NRS, and VAS (P <0.01). Analysis of the short and long follow-up subgroups indicated delayed improvement in PD-related pain. These findings (a) show the efficacy of STN-DBS on PD-related pain and provide higher-level evidence, and (b) implicate delayed improvement in PD-related pain, which may help programming doctors with supplement selecting target and programming. Systematic Review Registration: This study is registered in Open Science Framework (DOI: 10.17605/OSF.IO/DNM6K).